2006
DOI: 10.1007/s11307-006-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Existence of Quantum Metabolic Values in Non-Hodgkin’s Lymphoma by 2-Deoxy-2-[F-18]fluoro-d-glucose Positron Emission Tomography

Abstract: Distinct quantum metabolic values of -1 and 0 were noted in NHL. Aggressive NHL has a more negative value (or higher glucose sensitivity) than that of indolent and, thus, is more susceptible to extreme glucose variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Retrospective analyses have found that poor survival was associated with poor performance, an elevated level of lactate dehydrogenase (LDH), the presence of B symptoms, local tumor invasiveness, paranasal extension, regional lymph node involvement, and a high EBV DNA titer (6,7,(9)(10)(11). 18 F-FDG PET has been used increasingly to monitor treatment and follow-up in patients with lymphoma (12)(13)(14)(15)(16). Because the intensity of tumor 18 F-FDG uptake can distinguish between indolent and aggressive forms of lymphomas (17,18), 18 F-FDG PET can be used to identify the subset of patients who might respond to chemoradiation therapy.…”
Section: Ext Ranodal Natural Killer/t-cell Lymphoma (Enktl)mentioning
confidence: 99%
See 4 more Smart Citations
“…Retrospective analyses have found that poor survival was associated with poor performance, an elevated level of lactate dehydrogenase (LDH), the presence of B symptoms, local tumor invasiveness, paranasal extension, regional lymph node involvement, and a high EBV DNA titer (6,7,(9)(10)(11). 18 F-FDG PET has been used increasingly to monitor treatment and follow-up in patients with lymphoma (12)(13)(14)(15)(16). Because the intensity of tumor 18 F-FDG uptake can distinguish between indolent and aggressive forms of lymphomas (17,18), 18 F-FDG PET can be used to identify the subset of patients who might respond to chemoradiation therapy.…”
Section: Ext Ranodal Natural Killer/t-cell Lymphoma (Enktl)mentioning
confidence: 99%
“…18 F-FDG PET has been used increasingly to monitor treatment and follow-up in patients with lymphoma (12)(13)(14)(15)(16). Because the intensity of tumor 18 F-FDG uptake can distinguish between indolent and aggressive forms of lymphomas (17,18), 18 F-FDG PET can be used to identify the subset of patients who might respond to chemoradiation therapy. This may affect the prognostic stratification and clinical management of patients with lymphoma.…”
Section: Ext Ranodal Natural Killer/t-cell Lymphoma (Enktl)mentioning
confidence: 99%
See 3 more Smart Citations